Health literacy among pharmacy visitors in the Netherlands. (27th May 2015) - Koster, Ellen S.; Philbert, Daphne; Bouvy, Marcel L.
Abstract Purpose Health literacy is defined as the ability to obtain, understand and apply information to make appropriate health decisions. Most health literacy research has been performed in the USA. Our objective was to study the prevalence of limited health literacy among adult pharmacy visitors in the Netherlands and to assess the association between health literacy and understanding of drug label information. Methods A cross‐sectional study was performed in community pharmacies belonging to the Utrecht Pharmacy Practice network for Education and Research. Adult pharmacy visitors (aged ≥18 years) were approached in the pharmacy waiting area and invited for a brief interview including the newest vital sign, a validated health literacy assessment measure and questions about understanding of standard drug label instructions. Results A total of 984 pharmacy visitors were included in the study: 63% were women, mean age was 56 years and the majority was of native origin (84%). Based on newest vital sign scores, 52% had limited health literacy skills. Pharmacy visitors with limited health literacy skills had significantly lower understanding of drug label instructions (p < 0.001). Conclusion Approximately half of the pharmacy visitors in this study had limited health literacy skills. These individuals experienced more difficulties understanding drug label instructions. These findings emphasize the need to identify patients with limited health literacy skills, as these patients might be at increased risk for drug‐related problems caused by misunderstanding of information. Copyright © 2015 John Wiley & Sons, Ltd.